An analytical model of collections and their catalogues - Heaney, M (2001)
This work arises from the UKOLN proposal to the Research Support Libraries Programme Collection Development: Study, Recommendation, Specification, which undertakes to ‘refine our current approach based on a more thorough modelling of collections and their catalogues’, and to validate the approach by working with RSLP projects and others to describe their collections. The elaboration of the model itself has been carried out with financial support from OCLC.